Multiple legumain isoenzymes in ticks. Issue 2 (February 2018) - Hartmann, David; Šíma, Radek; Konvičková, Jitka; Perner, Jan; Kopáček, Petr; Sojka, Daniel
Graphical abstract: Highlights: Ixodes scapularis genome encodes for nine legumain-like enzymes (IsAEs). Expression profiling reveals two dominant gut-specific enzymes, IsAE1 and IsAE2. Both are structurally identical but differentially expressed. Ixodes ricinus females are not affected by IrAE1 and IrAE2 RNA interference or vaccination. Phenotype markers are changed upon tick in vitro feeding with a legumain inhibitor. Abstract: By searching nucleotide databases for the North American Lyme disease vector, Ixodes scapularis, we have complemented the previously characterized European Ixodes ricinus legumain IrAE1 with a full set of nine analogous genes ( isae1-9 ). Six of these were PCR confirmed as genes present in all tick genomes tested. The absolute mRNA copy number examined by quantitative (q)PCR enabled expression profiling and an absolute comparison of mRNA levels for individual I. scapularis (Is)AEs in tick tissues. Four IsAEs (1, 2, 4, 9) were expressed solely in the gut and thus are proposed to be involved in host blood digestion. Expression qPCR profiling over developmental stages confirmed IsAE1, the direct analogue of previously characterized I. ricinus IrAE1, as the principle legumain transcript in partially engorged females, and demonstrated its strong regulation by on-host feeding in larvae, nymphs and females. In contrast, IsAE2 was the predominant gut legumain in unfed nymphs, unfed females and males. In-silico, IsAE1 and IsAE2 protein three-dimensional structural models displayed minimal differences in overall proenzyme structures, even in comparison with recently resolved crystal structures of mammalian prolegumain. Three functional studies were performed in I. ricinus with IsAE1/IsAE2 analogues: double IrAE1/IrAE2 RNA interference silencing, feeding of ticks on IrAE1+IrAE2 immunized hosts and in vitro membrane tick feeding on blood containing a legumain-specific inhibitor. The latter experiment led to reduced weights of fully engorged ticks and limited oviposition, and indicated the potential of legumain inhibitors for novel anti-tick interventions.